Characterization and functional analysis of a slow cycling stem cell-like subpopulation in pancreas adenocarcinoma - Dembinski, Jennifer L. (Springer Netherlands, 2009)
Evidence suggests that multiple tumors, including pancreatic adenocarcinoma, display heterogeneity in parameters that are critical for tumor formation, progression and metastasis. Understanding heterogeneity in solid tumors is increasingly providing a plethora of new diagnostic and therapeutic approaches. In this study, a particular focus was put on identifying a subpopulation of stem cell-like, slow cycling tumor cells in a pancreas adenocarcinoma cell lines. Using a label retention technique a subpopulation of slow cycling cells (DiI+/SCC) was identified and further evaluated in the BxPC-3 and Panc03.27 cell lines. These slowly cycling cells managed to retain the lipophilic labeling dye DiI, while the bulk of the cells (>94%) did not. The DiI+/SCC population, showed only a partial overlap with the CSC markers CD24(+)/CD44(+), CD133(+) and ALDH but they survived chemotherapeutic treatment, and were able to recreate the initial heterogeneous tumor cell population. DiI+/SCCs exhibited an increased invasive potential as compared with their non-label retaining, faster cycling cells (DiI−/FCC). They also had increased tumorigenic potential and morphological changes resembling cells that have undergone an epithelial to mesenchymal transition (EMT). Analysis of DiI+/SCC cells by real time PCR revealed a selective up-regulation of tell tale components of the Hedgehog/TGFβ pathways, as well as a down-regulation of EGFR, combined with a shift in crucial components implied in EMT. The presented findings offer an expanded mechanistic understanding that associates tumor initiating potential with cycling speed and EMT in pancreatic cancer cell lines. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s10585-009-9260-0) contains supplementary material, which is available to authorized users.